Highly Sensitive Detection of Complicated Mutations of Drug Resistance in Mycobacterium tuberculosis Using a Simple, Accurate, Rapid, and Low‐Cost Tailored‐Design Competitive Wild‐Type Blocking Assay. Issue 3 (22nd January 2023) - Yan, Mengqiu; Zhao, Zhenzhen; Wu, Tao; Liu, Tangyuheng; Xu, Gaolian; Xu, Hong; Ying, Binwu
Abstract: Establishing simple, rapid, and highly sensitive molecular assays is crucial for timely diagnosis and effective treatment of drug‐resistant tuberculosis. However, current genotypic drug susceptibility testing (DST) still encounters enormous challenges including lower sensitivity than phenotypic DST and insufficient accuracy. Herein, a simple, low‐cost, multiplex real‐time polymerase chain reaction‐based assay is established to achieve highly sensitive detection of low‐abundant mutants through competitive wild‐type blocking (COWTB). Analytical performance of the COWTB assay can achieve 1% or even 0.1% mutants under background of 10 000 wild‐type genomes/test. Furthermore, clinical practice feasibility is evaluated to identify resistance to rifampicin (RIF), isoniazid (INH), and streptomycin (SM) on 92 actual clinical samples, its sensitivity is 93.8% for RIF and 100% for INH and SM, and specificity is 100% each for RIF, INH, and SM when using DNA sequencing as the reference standard. In comparison, the sensitivity of reverse dot blotting assay commonly used in clinics is 93.8%, 90.0%, and 84.6%, and the specificity is 96.1%, 98.6%, and 100% for RIF, INH, and SM, respectively. Importantly, the COWTB assay can also be applicable for other drug‐resistant mutations and pave a promising detection strategy to fill the gap between phenotypic and genotypic DST for detecting low‐abundant drug‐resistant M. tuberculosis . Abstract : A tailored‐design competitive wild‐type blocking (COWTB) assay is established for highly sensitive detection of 1% or even 0.1% mutant ratio in drug‐resistant Mycobacterium tuberculosis . The sensitivity of COWTB assay is 93.8% for rifampicin and 100% for isoniazid and streptomycin, and specificity is 100% each for the three antituberculosis drugs when evaluating 92 clinical samples on conventional polymerase chain reaction platform.